C.A. Nothardbiblioteek - J. Swart (AOSIS, 1988)
As instructed by the Central Board of the South African Nursing Association during 1985, an investigation was launched into the function of the C.A. Not hard Library, namely to provide optimal information to members. The underlying philosophy concerned with the establishment of the library was to provide a service which is not available elsewhere. The investigation revealed however, that various training institutions in the country meet this need. As a result of the findings, as presented in the article, the C.A. Northard Library was closed on 1 December 1985 as a lending library. A unique Nursing reference library is being established in its place, with the emphasis in the future on the S. A. Nursing Association's role in the promotion of Nursing research.